Willingness to pay and actual purchase decision for organic agriculture products in Vietnam - Dung Tien Luu (Universitas Islam Indonesia, 2019)
This article aims to investigate the determinants of willingness to pay and the actual purchase decision of organic agriculture products among consumers in Vietnam, one of the emerging markets. The study uses primary survey data of 210 consumers based on the logit and ordered logit regression models. Findings/Originality: The results confirmed that consumers' perceptions of external factors and product attributions, external factors (processing, packaging, and labelling, certification, supply of product), perceived health and nutrition of products, socioeconomic characteristics significantly influence on consumer’s willingness to pay and actual purchase decision for organic foods in the context of Vietnam market. These results of the study provided insights for marketers on the key variables that could be used for promoting more widespread consumption of organic foods in the country.